Review of highly charged tungsten spectroscopy research using low energy EBITs at the Shanghai EBIT laboratory. (28th May 2015) - Qiu, M L; Li, W X; Zhao, Z Z; Yang, Y; Xiao, J; Brage, T; Hutton, R; Zou, Y
Abstract: We present an overview of recent work on the spectroscopy of tungsten ions, related to tokamak edge plasma. The spectra were recorded from the newly-built low energy electron beam ion traps (EBITs) in the Shanghai EBIT laboratory. By analyzing the spectra with the help of accurate theoretical calculations, using state-of-the-art techniques, we were able to identify term and fine structure splittings in the ground and the first excited configuration for a number of charge states. The theoretical models included a careful study of correlation and showed an excellent agreement with our experimental results for transition energies and rates. Some metastable levels which have extremely long lifetime and high population were found, and the influences of these levels on the charge state distribution of tungsten ions in tokamaks are discussed.